Eccentric connectivity index of unicyclic graphs with application to cycloalkanes - Haoer, Raad Sehen; Mohd Atan, Kamel Ariffin; Khalaf, Abdul Jalil Manshad; Hasni @ Abdullah, Roslan (IEEE, 2015)
Let G be a simple connected molecular graph. The eccentric connectivity index ξ(G) is defined as ξ (G) = ∑ν∈V(G)deg (ν)ec(ν), where deg(ν) denotes the degree of vertex v and ec(ν) is the largest distance between ν and any other vertex u of G. In this paper, we construct the general formulas for the eccentric connectivity index of unicyclic graphs with application to cycloalkanes.